Mutational and cytogenetic analyses of 188 CLL patients with trisomy 12: A retrospective study from the French Innovative Leukemia Organization (FILO) working group. Issue 11 (11th September 2018) - Roos‐Weil, Damien; Nguyen‐Khac, Florence; Chevret, Sylvie; Touzeau, Cyrille; Roux, Clémence; Lejeune, Julie; Cosson, Adrien; Mathis, Stéphanie; Feugier, Pierre; Leprêtre, Stéphane; Béné, Marie‐Christine; Baron, Marine; et al.
Abstract: Trisomy 12 (tri12) is the second most frequent chromosomal aberration (15%‐20%) in chronic lymphocytic leukemia (CLL). Tri12 confers an intermediate prognosis but is a heterogeneous entity. We examined whether additional mutational or chromosomal alterations might impact tri12 patient outcomes. This retrospective study, carried out by the French Innovative Leukemia Organization, included 188 tri12 patients with comprehensive information on immunoglobulin heavy chain ( IGHV ) gene status, karyotypic/FISH abnormalities, and NOTCH1, TP53, SF3B1, and MYD88 mutations. The main cytogenetic abnormalities associated with tri12 were del(13q) (25%), additional trisomies (14%) (including tri19 (10%) and tri18 (4%)), 14q32 translocations (10%), del(17p) (6.5%), del(14q) (4%), and del(11q) (4%). Unmutated (UM) IGHV, NOTCH1, and TP53, mutations were identified in respectively 66%, 25%, and 8.5% of cases. Multivariate analyses showed that additional trisomies (HR = 0.43, 95% CI = 0.23‐0.78, P = .01) were associated with a significantly longer time to first treatment in Binet stage A patients and with a lower risk of relapse (HR = 0.37, 95% CI = 0.15‐0.9, P = .03) in the overall tri12 population. Binet stage B/C, TP53 disruption, and UM IGHV status were associated with a shorter time to next treatment, while Binet stage B/C (HR = 4, 95% CI = 1.6‐4.9, P = .002) and TP53 disruption (HR = 5, 95% CI = 1.94‐12.66, P = .001) conferred shorter overall survival in multivariate comparisons. These data indicate that additional cytogenetic and mutational abnormalities, and particularly additional trisomies, IGHV status, and TP53 disruption, influence tri12 patient outcomes and could improve risk stratification in this population.